Early Puerperal Complications - A Prospective Clinical Study on Caesarean Deliveries (Journal of Dhaka Medical College, 2018)
Introduction : when a healthy pregnant woman with no obstetric or medical risk factors goes into spontaneous labour, she should anticipate a normal delivery. But still 580, 000 women in the world die from pregnancy and childbirth each year.1 Lack of attention to postpartum care in developing countries is neglected tragedy and requires immediate attention. This study evaluates the incidence of complications of early puerperium and also focuses the specific types of complications and to detect the risk factors associated with these complications.Aims and objectives : Main aim of the study is to evaluate the common complications in early puerperium with special attention to identify the risk factors.Materials and method : This study was carried out in Dhaka Medical College Hospital and Sir Sallimullah Medical College Hospital within the period of March ’2004 to August’ 2004. Two hundred patients were selected for this study who were delivered by caesarean section in these two institutions and complications occurring within 7 days excluding first 24 hours. Patients delivered outside the hospital and with known medical diseases were excluded from this study. Detailed history taking and appropriate clinical examination and specific investigations were done for diagnosis of complications. All relevant informations was noted in prescribed data sheet and results were tabulated and statistical analysis was done.Results : Among 200 cases only 44(22%) cases had early puerperal morbidity.Most of the patients who suffered complications underwent caesarean section for obstructed labour and fetal distress who had trial at home. Many of the patients suffered from wound infection and endometritis (40.9%). Among patients, age group -